IJCM_159A: Descriptive study on determinants of indoor air pollution and its perceived impact on health among residents of urban field practice area of a tertiary care hospital - Subhashrao Kulkarni Kulbhushan; Mundada Vinod D. (Wolters Kluwer Medknow Publications, 2024)
Background: Indoor air pollution is the presence of unwanted substances in the indoor at concentration toxic to health. According to WHO, around 3.8 million deaths occur due to indoor air pollution every year. Very few studies have addressed indoor air pollution. Thus, this study aimed at determinants of indoor air pollution and its perceived impact on health among residents. Objectives: 1. To study the determinants of indoor air pollution among residents of urban field practice area of a tertiary care hospital. 2. To study the perceived impact of indoor air pollution on health among residents of urban field practice area of a tertiary care hospital. Methodology: A community-based cross-sectional study conducted among 105 households of urban field practice area of a tertiary care hospital during August 2023 to October 2023. Data collection was done using predesigned pre tested interview schedule which consists of sociodemographic characteristics, sources of indoor air pollution, checklist of contributory factors of air pollutants and related symptoms/diseases. Results: About 45.7% households had second hand smoke in house. Smoke from the neighbourhood troubled 38% respondents. 33.3% households had IAP owing to vehicular exhausts. 75.2% houses were having absence of cross ventilation and 68.5% houses were poorly ventilated. Also, 60.9% houses reported overcrowding. About 53.3% complained of having at least one symptom of IAP. Conclusion: Majority of the households were exposed to IAP due to second hand smoke, neighborhood smoke while absence of cross ventilation accented it. Efforts to address IAP should be made to protect residents from adverse health effects.